A study on course timetabling for FCSIT - Bong, Chia Lih (Universiti Malaysia Sarawak (UNIMAS), 2014)
This thesis proposes a heuristic method for solving faculty course timetabling problem. The algorithm can be divided into two stages. The first stage is course grouping, which aiming to reduce the problem size. The second stage is timeslot and venue allocation according to the groups generated from first stage. The larger classes will be allocated first due to limited resources on large lecture hall. Timetable based on real data from SEM 1 2011/2013 was generated by this automated algorithm. The computational result shows that the algorithm was fast in generating solution. There also no class clashes generated in this case study. Besides, most of the students' timetables were evenly distributed.